The Effect Of Internal Control and human Resource Competence on Fraud Prevention with Wisthleblowing System as a Moderating Variable - Ilmiana Nur Isfani, Mutiara; Nur Intan Fadhilah, Azkia (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This research aims to obtain emprocal evidence about the effect of internal control and human resource competence on fraud prevention with the Whistleblowing sytem as a moderating variable. Design/methodology/approach – This research uses quantitative research. This research was conducted using a questionnaire distributed to employees who are members of PT. Bank Pembangunan Daerah Jawa Barat dan Banten, Tbk Bekasi Branch Office, namely ass 110 questionnaire distributed via email and social media. Each questionnaire distributed contaned 54 statements to be answered by respondents. From the distirbution of questionnaire conducted, 110 respondents were obtained who provided answer to get the results of this study, the researcher used PLS SEM Vresion 3.0. Findings – The results of study found that internal control has a positive and significant on fraud prevention, human resource competence has a positive and significant on fraud prevention, the whistleblowing system can strengthen the relationship between internal control and fraud prevention, the whistleblowing system cannot strengthen the relationship between human resource competence and fraud prevention. Research limitations/implications – This research introduces innovative variables in fraud prevention including internal control, human resource competence, and whistleblowing system.